Sensibilização e alergia ao látex em crianças e adolescentes com mielomeningocele - Sá, Adriano Bueno de [UNIFESP] (2010)
Background: Latex allergy is responsible for numerous allergic reactions in sensitized individuals. Objectives: To evaluate the prevalence of sensitization and latex allergy and food in children and adolescents with myelomeningocele and to identify possible risk factors associated with them. Methods: The study included 55 children and adolescents previously diagnosed with myelomeningocele treated in the neurosurgery clinic of the Hospital São Paulo, UNIFESP-EPM. Patients were assessed using standard questionnaire, skin prick tests for aeroallergens, total latex, and food and determination of serum total and specific IgE to total latex and its recombinant fractions. Results: We found rates of 45% and 20% for sensitization and latex allergy, respectively, with 14.5% of sensitization to food, with no cases of food allergy. Twenty-four (43.6%) were atopic and the average age of first episode of reaction to latex was 44.5 months, with skin reaction the most frequent reported (72.7%). The food sensitization occurred for the following foods: potatoes, papaya, manioc, jackfruit, mango, pineapple, pear, tomato, avocado and chestnut. Serum total IgE greater than 200 KU/l were more frequent in patients allergic and sensitized. The agreement using the kappa test between latex skin test and specific IgE to total latex was strong and between skin test to latex or total latex specific IgE and fractions rHev b1, 3, 5, 6:01 and 6:02 were moderate or good. The fraction of specific IgE to latex detected in more than 50% of patients were rHev b1 (16/25 - 64%) followed by rHev b6.02 (14/25 - 56%). Statistically significant difference was found between the group of allergic and sensitive when compared to non-sensitized to the following variables: atopy, current rhinitis, angioedema, average number of surgeries, patients with four or more surgeries, use of valvule, presence of at least one test positive aeroallergen skin, presence of at least one skin test for food and total IgE greater than 200 KU/l. Multivariate analysis showed as significant: current asthma, angioedema, atopy and number of surgeries undergone. Conclusions: Our study documented high leves of sensitization and latex allergy. Despite the frequent presence of specific IgE antibodies to food, the presence of latex-fruit syndrome was not confirmed. The skin test with a standardized latex extract was safe and reliable for the diagnosis of latex allergy. The comparative analysis between the skin prick tests and determination of specific IgE to total latex showed total agreement between them. Specific IgE to fractions rHev b1, 3, 5, 6:01 and 6:02 were detected in more than 50% of children and adolescents with myelomeningocele allergic to latex. The number of surgeries for which patients underwent determined higher levels of specific IgE, especially rHev b5 and 6.01. The history of current asthma, prior angioedema, atopy and having undergone four or more surgeries were independent factors identified for latex allergy.